Effect of the fibre geometry on pull-out behaviour of HVFA mortar containing nanosilica - Shafaei, Yashar; Shaikh, Faiz; Sarker, Prabir (Elsevier BV, 2017)
It is essential to understand the single fibre pull-out response in order to understand and predict the behavior of fibre reinforced composites. Hook geometry can largely affect the post-crack behaviour of fibres in structural elements. There is limited data available on newly developed multi hooked end steel fibers. This paper presents results of single fibre pull-out tests of three types of hooked end steel fibres embedded in high volume fly ash (HVFA) mortar. Steel fibres were defined as double, triple or quadruple hooked based on their geometry. The results of this study indicates that the pull-out load of the steel fibres was increased with the increase of the number of bends at the ends. It was also observed that the extra hooks resulted in some plastic deformation of the fibres. The average pull-out load of the quadruple hooked fibre was 1.4 times higher than that of the average pull-out load of the double hooked fibre. Pull out strength was increased with the increase of the matrix strength. The compressive strength of the mortar was increased by 18% with the addition of 2% nanosilica (NS) and 10% microsilica (MS). Inclusion of these fine particles improved the bond between fibres and the mortar which consequently increased the pull-out load. The double hooked end fibre exhibited the smallest pull-out load among the three types of fibre studied. It was also observed that the pull-out load of all types of fibres increased with the reduction of fly ash (FA) content. Furthermore, results also demonstrate that the addition of MS and NS increased the pull-out load of steel fibres in HVFA mortar up to 31%.